First records of Nacerdes melanura (Linnaeus 1758) and Xanthochroina auberti (Abeille de Perrin 1876) (Coleoptera: Oedemeridae) from Israel - Rittner, Oz; Nir, Assaf (Zootaxa, 2014)
Nacerdes melanura (Linnaeus 1758) and Xanthochroina auberti (Abeille de Perrin 1876) are recorded from Israel for the first time.